2022
DOI: 10.1186/s12875-022-01661-7
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in the therapeutic relationship: emotional labour in the response to child abuse and neglect in primary healthcare

Abstract: Background Child abuse and neglect (child abuse) is a prevalent public health issue linked to survivors experiencing a higher risk of health issues such as obesity, heart disease and major depression. Given the significant impact of child abuse on health, general practitioners (GPs) and primary care nurses (nurses) are well-placed to respond to child abuse. However, research shows that responding to child abuse is difficult for health practitioners, especially the act of reporting child abuse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The emotional toll associated with working with families was found to have implications in all phases of parent involvement, including when engagement was fractured. Similar to another study [37] the current study found when the working relationship between nurse and family ends without warning the emotional impact on the nurse is evident. The critical importance placed on honesty in the early formation of the relationship has been emphasised and must remain equally important across all phases of intervention.…”
Section: Conclusion Phase: Uncertain Endingssupporting
confidence: 88%
See 2 more Smart Citations
“…The emotional toll associated with working with families was found to have implications in all phases of parent involvement, including when engagement was fractured. Similar to another study [37] the current study found when the working relationship between nurse and family ends without warning the emotional impact on the nurse is evident. The critical importance placed on honesty in the early formation of the relationship has been emphasised and must remain equally important across all phases of intervention.…”
Section: Conclusion Phase: Uncertain Endingssupporting
confidence: 88%
“…In an Australian study of primary health care providers [37] the health professionals regarded making a child protection report as an act of betrayal, rather than a sign of trust. However, recent research interest in this field, including this study herein, indicates that relationships are preserved, and that trust can be extended when honesty is prioritised during the enrolment phase [13].…”
Section: Enrolment Phase: Honesty In Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…This patients' charter specifies the privacy, rights and expectations that patients have as part of their human basic rights (Kalyuzhny et al, 2020 ). When their privacy is compromised, even if accidentally, patients may feel they have lost their dignity, destroying the therapeutic relationship that exists between nurses and patients (Kuruppu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%